Natural gas as a bridge to hydrogen transportation fuel: Insights from the literature. (April 2018) - Ogden, Joan; Jaffe, Amy Myers; Scheitrum, Daniel; McDonald, Zane; Miller, Marshall
Abstract: Natural gas has been proposed as a possible "bridge" fuel to eventual use of hydrogen in zero emission fuel cell vehicles. This literature review explores whether the natural gas system might help enable a transition to longer-term use of hydrogen in transportation. Two transition strategies are reviewed: adapting natural gas refueling infrastructure for future use with H2 and blending renewable hydrogen into the NG system. Our review suggests it is not attractive to re-purpose or overbuild NG fueling station equipment for future hydrogen service. Transporting H2/NG blends in the NG pipeline grid appears technically possible at modest fractions of 5–15% hydrogen by volume, but requires careful case by case assessment and could be expensive. Blending does not enable major reductions in GHG emissions from transport, unless "green" hydrogen can be cost effectively separated from the blend and delivered to highly efficient fuel cell vehicles. Ultimately, blend limits could make it difficult to utilize the existing NG system to deliver hydrogen at the scale needed to achieve deep cuts in transportation related GHGs. A dedicated renewable hydrogen system would be needed, if zero emission fuel cell vehicles play a major role in a future low carbon world. Highlights: NG/H2 synergies constrained by market, technical, economic, network design factors. Costs unattractive to overbuild natural gas stations for hydrogen compatibility. Using hydrogen in natural gas grid is complex, renewable methane may be easier fit. Long term H2 demand might exceed capacity of NG grid to deliver H2 in blend. In 2 degree world, a dedicated H2 refueling infrastructure would be needed.